Plasmacytoid Dendritic Cells: Neglected Regulators of the Immune Response to Staphylococcus aureus - Bekeredjian-Ding, Isabelle; Greil, Johann; Ammann, Sandra; Parcina, Marijo (Frontiers in Immunology, 2014)
Plasmacytoid dendritic cells (pDC) are a rare subset of leukocytes equipped with Fcgamma and Fcepsilon receptors, which exert contrary effects on sensing of microbial nucleic acids by endosomal Toll-like receptors. In this article we explain how pDC contribute to the immune response to Staphylococcus aureus. Under normal circumstances the pDC participates in the memory response to the pathogen: pDC activation is initiated by uptake of staphylococcal immune complexes with IgG or IgE. However, protein A-expressing S. aureus strains additionally trigger pDC activation in the absence of immunoglobulin. In this context staphylococci exploit the pDC to induce antigen-independent differentiation of IL-10 producing plasmablasts, an elegant means to propagate immune evasion. We further discuss the role of type I interferons in infection with S. aureus and the implications of these findings for the development of immune based therapies and vaccination.